Digital Innovation in Zakat Collection at the National Zakat Collection Agency of North Lombok Regency - Arifin, Ernaldo Fikrul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The development of digital technology has encouraged zakat institutions to transform their fundraising strategies. This study aims to analyze the digital innovations implemented by the National Zakat Agency (BAZNAS) of North Lombok Regency to increase the effectiveness of zakat, infaq, and alms (ZIS) collection. The research method used a qualitative approach through observation, documentation studies, and in-depth interviews with BAZNAS administrators and the community. The results show that digital innovations through the BAZNAS Management Information System (SIMBA), digital payment channels such as QRIS and bank transfers, digital zakat campaigns, and the use of the official website play a significant role in increasing the transparency, effectiveness, and accessibility of ZIS services. Digital strategies have been proven to strengthen public trust, simplify transaction processes, and reach a younger generation familiar with technology. These innovations also support modern fundraising theory, which emphasizes building an institutional brand image and increasing muzaki engagement through an adaptive approach.